PERLINDUNGAN HUKUM TERHADAP PEMEGANG SERTIPIKAT ELEKTRONIK DALAM SISTEM PERTANAHAN DI INDONESIA - Jamil, Jamil (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2025)
The advancement of information technology has driven land administration reform through the implementation of electronic certificates by the Ministry of Agrarian Affairs and Spatial Planning/National Land Agency (ATR/BPN). While this innovation aims to improve efficiency and transparency, it raises new legal issues, particularly regarding legal protection for certificate holders in cases of data misuse, system hacking, or ownership disputes. This study analyzes the available legal protections for electronic certificate holders and identifies regulatory weaknesses and implementation challenges in the electronic land system. The research employs a normative juridical method with legislative and conceptual approaches, supported by a literature review of regulations, legal doctrines, and related literature on the digitization of state documents. The findings reveal that although electronic certificates are legally recognized under ATR/BPN Regulation No. 1 of 2021, No. 3 of 2023, and the ITE Law, the mechanisms for protecting rights holders remain inadequate. There is no clear recovery procedure in cases of data manipulation or system failures, nor a dedicated compensation system or specialized dispute resolution body. The study recommends reforming digital land policies through regulatory strengthening, cybersecurity integration, and institutional capacity building to ensure comprehensive land rights protection in the digital era.